RELIGIOUS APPROACHES TO TERRORISM PREVENTION: AN ANALYSIS OF MAQASHID SYARIAH ON THE STRATEGY OF THE NORTH SUMATERA FKPT - Nandani Zahara Mahfuzah; Ansari Yamamah; Ramadhan Syahmedi Siregar (SOSIOEDUKASI, 2025)
The phenomenon of terrorism in Indonesia, particularly in the city of Medan, poses a serious challenge that threatens social stability, national security, and national values. In this context, the North Sumatra Terrorism Prevention Coordination Forum (FKPT) acts as an extension of the National Counterterrorism Agency (BNPT) in implementing prevention programs based on local wisdom and a humanistic approach. This study aims to gain a deeper understanding of the FKPT North Sumatra's strategies in countering terrorism in the city of Medan through an approach that is not only functional but also theological, by examining these efforts from the perspective of maqāṣid al- syarī‘ah. This research uses a qualitative method with field research (empirical). Data is obtained through observation, in-depth interviews, and documentation studies of FKPT programs and the involvement of stakeholders such as religious leaders, academics, and local communities. The results of the research show that FKPT implements an integrated strategy, including educational, cultural, collaborative, and digital approaches. These efforts are carried out through moderate religious literacy, the involvement of women and youth, and the dissemination of peaceful narratives on social media and in arts and culture. Thisstrategy is not only in line with state policy but also reflects the implementation of maqāṣid al-syarī‘ah in protecting religion, life, intellect, lineage, and property. Thus, the FKPT North Sumatra strategy demonstrates that terrorism prevention can be achieved not only through repressive approaches but also through strengthening religious and national values that prioritize the public good.